Original paperRye grains and the soil derived from under the organic and conventional rye crops as a potential source of biological agents causing respiratory diseases in farmers - Żukiewicz-Sobczak, Wioletta A.; Cholewa, Grażyna; Krasowska, Ewelina; Chmielewska-Badora, Jolanta; Zwoliński, Jacek; Sobczak, Paweł (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Due to the specific work environment, farmers are exposed to various biological occupational hazard. Among these factors significant are fungi present in the grain and also in the soil. The fungi may be the cause of human diseases including skin infections, asthma, allergic rhinitis and many others. Aim: The aim of this study was to quantify and identify species of fungi colonizing rye grain samples and the soil under cultivation. Material and methods: The material consisted of grain and soil samples from two agricultural systems: organic and conventional.To determine the concentration and composition of fungi in collected samples, two media: Malt Agar (MA, Becton, Dickinson and Company) and Potato Dextrose Agar (PDA, Becton, Dickinson and Company) were used.The composition of species in fungal flora was determined using macroscopic and microscopic methods. The isolates of fungi were ranked in the appropriate classes of biosafety BSL. Results : The most frequently isolated fungi from organic rye grain, regardless of the media used, were species: Aureobasidium pullulans and Alternaria alternata. In conventional farms, most species isolated from rye grain were: Aureobasidium pullulans, Cladosporium oxysporum, Alternaria alternata and yeast-like fungi. Most often species isolated from the soil was Penicillium citreo-viride. Conclusions : All the results of the research demonstrate the potential hazard to the health of people working in agriculture. Significant exposure of this professional group is associated with the presence of harmful biological agents present in the grain and soil from its cultivation.